Students' Ability in Translation Techniques (English-Gorontalo): Subtitle of Orion and The Dark Film - Dama, Idrus; Idrus, Asri (Institut Agama Islam Negeri Palopo, 2024)
This study analyzes students' ability to apply translation techniques from English to Gorontalo based on the subtitles of the film